Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
[tex]2x-\frac{1}{6}=\frac{2(x-3)}{3}+1\ \ \ \ |multiply\ both\ sides\ by\ 6\\\\6(2x)-6(\frac{1}{6})=6\left(\frac{2x-6}{3}\right)+6(1)\\\\12x-1=2(2x-6)+6\\\\12x-1=2(2x)+2(-6)+6\\\\12x-1=4x-12+6\\\\12x-1=4x-6\ \ \ \ |add\ 1\ to\ both\ sides\\\\12x=4x-5\ \ \ \ \ |subtract\ 4x\ from\ both\ sides\\\\8x=-5\ \ \ \ |divide\ both\ sides\ by\ 8\\\\\boxed{\boxed{x=-\frac{5}{8}}}[/tex]
2x - 1 = 2(x-3)
6 3 + 1
2x - 1 = 2x - 6
6 4
4(2x - 1) = 6(2x-6)
8x - 8 = 12x - 36
-8x -8x
-8 = 4x - 36
+36 +36
28 = 4x
28 = 4x
4 4
7 = x
6 3 + 1
2x - 1 = 2x - 6
6 4
4(2x - 1) = 6(2x-6)
8x - 8 = 12x - 36
-8x -8x
-8 = 4x - 36
+36 +36
28 = 4x
28 = 4x
4 4
7 = x
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.